Improving systematic teaching and learning in folk music kantele pedagogy : a study of student-centredness and pedagogical tact in higher music education - Lehto, Laura (Taideyliopiston Sibelius-Akatemia, 2026)
With this study I bring ideas how to improve systematic teaching in folk music kantele pedagogy in higher education and try to find its connection between the concepts of student-centredness and pedagogical tact. I will discuss topics such as structuredness and openness, lesson planning, teaching resources, continuity, technical versus artistic expression devel-opment, and stereotypes. My research question is: how to improve systematic teaching and learning in kantele pedagogy from the standpoint of student-centredness and pedagogical tact in higher education? The empirical interview data was collected by three interviews with small kantele and kannel teachers and musicians from Estonia and Finland. The data was analysed through the concepts of pedagogical tact and student-centredness before the discussion on the following categories: structure and openness in kantele pedagogy; pedagogical materials and systematicity; supporting student’s professional development and the development of kantele pedagogy in general. The main findings that came out from the research were that openness in folk music teaching is valuable for many reasons. The story behind the player; communication with the audience during the concerts and finding own’s artistic expression with that heritage are few examples of it. Balancing between structure and freedom in lesson planning can mean to leave the lesson situation open. It helps to be more present in the situation, opening up opportunities that would help students discover different ways to pursue their goals. Structuredness and openness are not opposites, but it’s still important to discuss about the values and the goals in folk music pedagogy, because they might be contradictory. Though the methods of learning folk music differ from classical music, they are formal, because there is the research-oriented aspect behind it. There is no need to standardize everything, simply because the teaching takes place in academy; in fact, the traditional music brings individuality in it.
Keywords: pedagogiikka; opetus; musiikkikasvatus; kantele; korkeakouluopetus; kansanmusiikki; musiikkipedagogiikka; systemaattinen pedagogiikka; student-centeredness; fi=kansanmusiikki|sv=folkmusik|en=Folk Music|